Center-Pivot-Irrigated Soybean Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2004)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated soybean production in western Kansas.
MF586_2004_10
Keywords: MF586; Economics; Crops; MF